Pengaruh Kepemimpinan Kepala Desa terhadap Partisipasi Masyarakat dalam Pembangunan Desa Sruwi Kecamatan Winongan Kabupaten Pasuruan - Alfi Nuridina; Ratna Pudyaningsih; Eni Erwantiningsih (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Leadership is the ability to persuade or influence others to achieve certain goals and the authority to establish responsibility. The role and community is consciously and voluntarily in the stage of decision making, implementation of activities, monitoring and evaluation, as well as the use of development results from the development process is called "community participation". The population used is the community of Sruwi village with a sample of 100 respondents with a sampling technique using non probability techniques with slovin formulas, the division method using Random sampling Technique where researchers divided into several groups. Analysts used are Instrument Test, Description Analysis, Classic Assumption Test, Simple Linear Regression Analysis, Coefficient Determinant Analysis, Koofisien Correlation And Hypothesis Tests. The results showed that 1) Leadership had a partial effect on community participation with a value of sig.0,000 <0.05 and the value of count> t table is 15.763> 1.984 2) There is a relationship and influence between leadership variables and participation with a value of 0,000 <0.05. With the value of pearson correlation 0,847 which means correlation relations rates are very strong.